Portraits from the second half of the 18th century in Croatia – witnesses of clothing forms and fashion influences of rococo - Katarina Nina Simončić (University of Belgrade, 2016)
his paper will attempt to analyze the clothing from the rococo period and underline fashion as an important segment in the reconstruction of a specific style era. Based on conserved portraits from the second half of the 18th century, as well as rare artifacts of clothing from the period found in Croatia, a description of primarily women’s types of clothing, accessories and the terms used to describe them will be given. Influences had, primarily through cultural and trade routes, come from the fashion capital of the period – France, and fashion innovations and the intensity of their changes were under the influence of the personal style first of Madame de Pompadour and afterwards Marie Antoinette. Croatia, which had at the time been part of the Habsburg monarchy and under the Republic of Venice, tended toward French influences in fashion, which represents a considerable move from the prior influence of Italian and German style.